DETERMINAN PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT (Pada Perusahaan Sektor Keuangan Yang Terdaftar Di BEI Tahun 2015-2017) - Nova Istiqomah; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT                The purpose of this study is 1. To provide empirical evidence of the effect of company size on ERM. 2. Provide empirical evidence of the effect of Leverage on ERM. 3. Provide empirical evidence of the influence of the auditor's reputation on ERM disclosures. 4. Provide empirical evidence of the effect of profitability on ERM disclosures.               The population in this study was a banking sector company that published a report on the listed on the IDX. The method collected in this study is by using journals and analytical methods. With the t test the Enterprise Risk Management variable is influenced by profitability, leverage, profitability and firm size but is not influenced by the reputation of the auditor Key word: Enterprise Risk Management, Company size, leverage, profitability, auditor reputation